Perancangan Sistem Penyaliran Tambang Pada PIT XYZ PT Karya Bhumi Lestari Jobsite PT Kartika Selabumi Mining Desa Kedang Ipil Kota Bangun II Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Bagus Hidayat; Windhu Nugroho; Ma Revia Oktaviani (International Forum of Researchers and Lecturers, 2025)
Water is one of the things that is very influential in the mining process, mining water is water that is at the location and/or comes from the process of mining activities, both mining and processing, including runoff water in the mining area. Surface runoff water is rainwater that overflows into mining areas and is not a result of mining activities. The open pit mining method will cause the formation of a large basin so that it has the potential to become a water storage area, both from surface runoff and groundwater. During extreme weather conditions with high rainfall, water from surface runoff can inundate the ground floor and cause the mining front to become muddy, which can hamper mining activities. Handling waterlogging in mining forts requires good pumping performance, as well as re-planning the mine drainage system for the mine progress area. So that mining activities run smoothly and the mining front is free from puddles of water after rain, the drainage system must be well designed. Based on research that has been carried out, the total area of ​​the Catchment Area is 52.14 Ha with a runoff discharge of 82,567.79 m³/month. The planned discharge using the MF-290 Pump with RPM 1600 is, 290.00 m³/hour or 123,540.00 m³/month. After comparing the MF-290, MF-385 and DND-200 pumps, the MF-290 pump was selected for use. This is because the fuel consumption of the MF-290 is smaller so it saves costs and it is also deemed sufficient to use the MF-290 pump. Pump Ratio on the MF-290 pump April 6.71. May 3.93, June 6.44, July 6.36 and August 8.83, which means the pump is safe to use because the ratio is >1.